A new species of Manekia Trel. (Piperaceae) in Northwest Colombia (2017)
ABSTRACT: Manekia is one of five lineages recognized today in the Piperaceae. All species of Manekia are scandent lianas with petiolar margins extending throughout the petiole or beyond it into the leaf blade, with spikes often restricted to very short sympodial branches, appearing axillar, solitary or geminate, with four staminate flowers, anthers almost sessile and fruits partially to fully immersed in the rachis. Species of Manekia are entirely restricted to the Neotropics. At present, six species of Manekia are accepted in the genus. A detailed examination of all known collections, including the type specimens of Manekia, as well as field work in several areas of the Neotropics, suggest the existence of several taxonomic novelties within the genus, one of which (Manekia betancurii) is here described, from the western slopes of the western Cordillera in the department of Antioquia, Colombia. The new species is distinguished from all other species of Manekia by densely pubescent stems, petioles, peduncles, and lower surfaces of the leaves, leaves 9 pinnately nerved, and the petiolar margins extending 0.2−0.8 cm into the leaf blade. The new species is described and illustrated, a discussion on its distribution and ecology is provided and its taxonomic affinities discussed. A dichotomous key of all species recognized in Manekia (including M. betancurii) is also provided.